Data associated with the manuscript "Methane in Lakes: Variability in Stable Carbon Isotopic Composition and the Potential Importance of Groundwater Input" - Schenk, Jonathan (Linköping University, 2021)
Data used to produce the figures and table in the manuscript "Methane in Lakes: Variability in Stable Carbon Isotopic Composition and the Potential Importance of Groundwater Input".

Data set 1: Data used for Figure 3, Figure 4, Figure 5 and Table 1.
Data set 2: Data used for Figure 6.
Data set 3: Data used for Figure 7.

The dataset was originally published in DiVA and moved to SND in 2024.
Data associated with the manuscript "Methane in Lakes: Variability in Stable Carbon Isotopic Composition and the Potential Importance of Groundwater Input"
Keywords: lakes; sjöar; groundwater; grundvatten; methane; metan; Environmental Sciences; Miljövetenskap